"Interpretasierigting" as eksegetiese hulp: Rut in wyer kontekste - LC Jonker (Acta Theologica)
This article shows how the investigation into the history of origin of the text itself, as well as the Wirkungsgeschichte thereof, can assist in determing a possible "direction of interpretation" in terms of which modern readers/hearers may interpret a particular text. The point of departure is that the Biblical text of the book of Ruth was repeatedly placed into new and wider contexts. These wider contexts provide an indication as to the process of continuous interpretation of this story. The task of the modern exegete is "to tune onto the wavelenght" of this process. The process of interpretation in modern communities of faith can be proceeded with responsibility in this way.